The influence of traffic noise on birds - Wiącek, Jarosław; Polak, Marcin; Kucharczyk, Marek; Zgorzałek, Sylwia (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The dynamic development of road infrastructure negatively influences the natural environment and animals using habitats near roads. The main negative effects of this process are primarily: loss and fragmentation of habitats. Another problem is an increase in pollutants and noise intensity in the vicinity of roads. An important problem is negative influence of traffic noise on animals and especially birds. Road noise generate by vehicles disturb vocal communication between birds, mainly in the time of pair formation and early incubation period. Difficulties in communication evoked by noise seem to be one of the main problems in functioning in noisy surroundings. The main functions of birds’ singing are related with territorial defence and mating a partner. Another important effect on birds’ functioning near roads results in the masking of important biological signals due to noise. Masking important signals for territorial defence or partner selection can have as a consequence a negative influence on reproductive success. Species of birds which emit low frequency sounds are particularly exposed to this negative impact. As a results of traffic noise the changes in the volume and frequency of emitted sounds during singing are observed. Some authors pay attention to such factors as local climate or habitat and vegetation structure, because they have an important influence on the propagation of traffic noise. Most of the studies carried out previously concerns the breeding season, and only a few works to describe the impact of noise on birds during migration or wintering. The most frequently reported problem for researchers is to assess the densities of breeding birds near the roadside. The majority of species react with a drop in numbers at roadsides. There are species which are also known to appear with higher density at roadsides. Usually this is related with a richer plant vegetation structure at roadsides and the appearance of the so-called “edge effect”. Some results indicate that bird density at forest peripheries can reach values 40% higher than in the deep forest. An explanation of causes for such a state of matters are the higher numbers of invertebrates found at forest edges. The important factor influencing bird populations breeding at roadsides is also nest predation. Noise and visual disturbance can modifying predator pressure near roads.